2021
DOI: 10.1055/a-1587-8859
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Butoxycarbonylation of Polybromo(hetero)arenes: A Practical Method for the Preparation of (Hetero)arenepolycarboxylates and -carboxylic Acids

Abstract: The palladium-catalyzed alkoxycarbonylation of (N-hetero)aryl multibromides were investigated systematically. The results show that cheap and readily available in-situ Pd(OAc)2/rac-BINAP catalyst can catalyze butoxycarbonylation of various (N-hetero)aryl multibromides efficiently, and obtain esters with moderate to high yield (59-94% yield). from which, two new compounds (4,4ꞌ-dibutoxycarbonyl-1,1ꞌ-bi-2-naphthol and Di-n-butyl [2,2'-bipyrimidine]-5,5'-dicarboxylate were first reported in this work. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Considering that the reaction went through a series of intermediates, the addition product was isolated with a small yield of 11.9%. Recently, Ji et al 34 found a novel approach to prepare triphenylene-2,3,6,7,10,11-hexacarboxylate via the palladium-catalyzed butoxycarbonylation of 2,3,6,7,10,11-hexabromotriphenylene (Scheme 1b). The synthesis route to triphenylene ester derivative was merely one step and the yield reached up to 60%, greatly improving the synthesis efficiency.…”
Section: Construction Of Pi-cofs Based On Star-shaped Electron-defici...mentioning
confidence: 99%
“…Considering that the reaction went through a series of intermediates, the addition product was isolated with a small yield of 11.9%. Recently, Ji et al 34 found a novel approach to prepare triphenylene-2,3,6,7,10,11-hexacarboxylate via the palladium-catalyzed butoxycarbonylation of 2,3,6,7,10,11-hexabromotriphenylene (Scheme 1b). The synthesis route to triphenylene ester derivative was merely one step and the yield reached up to 60%, greatly improving the synthesis efficiency.…”
Section: Construction Of Pi-cofs Based On Star-shaped Electron-defici...mentioning
confidence: 99%